SWITCHING APPARATUS FOR ELECTRICAL SYSTEMS AND CONTROL METHOD THEREOF - Villano, Massimiliano; Taborelli, Carlo (2025)
A switching apparatus for electrical applications comprising:- one or more electric poles;- for each electric pole, one or more fixed contacts and one or more movable contacts, wherein said movable contacts are reversibly movable between an uncoupled position, at which said movable contacts are decoupled from said fixed contacts, and a coupled position, at which said movable contacts are coupled with said fixed contacts;- an actuation assembly including an electromagnetic actuator and one or more opening springs operatively coupled to said movable contacts,wherein said electromagnetic actuator is adapted to provide actuation forces directed in such a way to move said movable contacts towards said coupled position,wherein said opening springs are adapted to provide actuation forces directed in such a way to move said movable contacts towards said uncoupled position,- a driving unit electrically connected to said electromagnetic actuator and adapted to feed said electromagnetic actuator with an excitation current to operate said electromagnetic actuator;- a control unit operatively coupled to said driving unit to control said driving unit,wherein said control unit is configured to determine whether said movable contacts are subject to undesired movements away from said coupled position, when said switching apparatus is in a closed state, based on the behaviour of an excitation current feeding said electromagnetic actuator,wherein said control unit is configured to command said driving unit to change the feeding of said electromagnetic actuator, if it is determined that said movable contacts are subject to undesired movements, when the switching apparatus is in closed state.